New risk factors and molecular landscapes of hepatic angiosarcoma in the Taiwanese population - Chung, Felicia Fei Lei *; Zavadil, Jiri (Wiley, 2024)
Hepatic angiosarcoma is a rare, highly aggressive malignancy of the liver. The tumorigenesis of hepatic angiosarcoma has been relatively understudied in terms of aetiology and molecular properties. A recent study published in The Journal of Pathology revealed a strong association between hepatic angiosarcoma incidence and chronic kidney disease, particularly in end-stage renal disease using population-based data from the National Health Insurance Research Database in Taiwan and an institutional cohort. The study also revealed enrichment in the mutational signature of aristolochic acid exposure and is the first reported observation of this mutational signature in human sarcomas. © 2023 The Pathological Society of Great Britain and Ireland.